Application and result of soil erosion estimation method based on geographic information system and remote sensing technology - ZHU Lei; HUANG Jing-feng; LI Jun (浙江大学学报. 农业与生命科学版)
This article mainly illustrated the application of soil erosion estimation method based on Geographic Information System (GIS) and remote sensing (RS) technology. Based on this two technology, the research made use of the Revised Universal Soil Loss Equation (RUSLE) to analyze the factors affecting on soil erosion and to clarify the spatial distribution's characteristics of soil erosion. The results indicated that the application of GIS and RS to investigation and inspection of soil erosion is feasible and efficient.